Home is Where the Triggers Are: Increasing Asthma Control by Improving the Home Environment - Krieger, James (Mary Ann Liebert, Inc., 2010)
Asthma remains the most common chronic condition of childhood. Strong evidence has linked exposure to allergens and other triggers commonly found in homes to allergen sensitization and asthma incidence and morbidity. A growing body of evidence has demonstrated that a home visit strategy that includes an environmental component that addresses multiple triggers through multiple interventions is effective. Such home visits reduce exposure to triggers, decrease symptoms and urgent health-care use, and increase quality of life. To make home visits widely available will require health-care payor reimbursement, government and health plan funding, training and certification of home visitors, and active referrals from health-care providers. However, a strategy based solely on education and behavior change is limited, because it cannot adequately reduce exposures due to adverse housing conditions. Therefore, approaches that address substandard housing are needed. These include remediation of existing housing and construction of new asthma-friendly homes. Most studies of remediation have made relatively narrow and focused improvements, such as insulation, heating, or ventilation. Outcomes have been mixed. Studies of new asthma-friendly homes are in their infancy, with promising pilot data. Further investigation is needed to establish the effectiveness of improving housing. A final strategy is improving housing quality through policy change, such as implementation of healthy housing guidelines for new construction, enhancement and increased enforcement of housing codes, and assuring smoke-free multi-unit homes. The combination of home visits, improved housing construction, and policy change has great potential for reducing the global burden of asthma.